General Trends of Business Career Management - Kharadze, Natalia; Paichadze, Nugzar; Paresashvili, Nino; Pirtskhalaishvili, Dea (European Journal of Economics and Business Studies, 2019)
Correct career management policies provide human resources with the ability to increase the required habits, skills, qualification capabilities and become recognizable. Personnel policy and career management are important and current issues, that’s why it has become an object of our research. The research was conducted in the "Human Potential Management" laboratory at the Faculty of Economics and Business of Ivane Javakhishvili Tbilisi State University. The research was conducted by an associate professor Natalia Kharadze. Associate Professors, PhD students and other students were involved in it. The questionnaire according to which the survey was carried out consisted of 32 questions and 125 options for an answer. The survey was attended by the respondents employed in Tbilisi, who were randomly selected in a short period of time. For the purpose of conducting a comprehensive research, SPSS statistical software package was used for statistical processing and data analysis. The questionnaire data discussed in the survey was filled by 560 respondents. Several hypotheses have been proved: Hypothesis HP1; Hypothesis HP3_1; Hypothesis HP3_2; Hypothesis HP3_3: hypothesis HP3_4; in which the correlation analysis has been used, Chi-squared test; While hypothesis HP2 has been used for single-factor dispersion analysis -One Way ANOVA, Cross tabulation analysis, test of homogeneity of variance (Levene). As a result of analyzing the survey data, we had the opportunity to formulate some recommendations that will allow the organizational head to reduce signs of discrimination.